Strength Mechanism and Influence Factors for Cold Recycled Asphalt Mixture - Tao Ma; Hao Wang; Yongli Zhao; Xiaoming Huang; Yuhui Pi (Advances in Materials Science and Engineering)
This study focused on the key factors affecting the tensile strength of cold recycled asphalt mixture with cement and emulsified asphalt. The specific surface areas and strength of RAP were analyzed. The interaction between the emulsified asphalt and cement was observed. Comprehensive laboratory testing was conducted to evaluate the influences of RAP, emulsified asphalt, and cement on the tensile strength of cold recycled asphalt mixture. It is found that although RAP is used as aggregates, its inner structure and strength are much different from real aggregates. The strength of RAP has decisive effect on the strength of cold recycled asphalt mixture. New aggregates and fine gradation design can help improve the bonding between RAP and binder. For emulsified asphalt, slow setting of asphalt can give sufficient time for cement to hydrate which is helpful for strength formation in the cold recycled asphalt mixture. The high viscosity of asphalt can improve the early strength of cold recycled asphalt mixture that is important for traffic opening in the field. Cement is an efficient additive to improve the strength of cold recycled asphalt mixtures by promoting demulsification of emulsified asphalt and producing cement hydrates. However, the cement content is limited by RAP.